2008
DOI: 10.1007/s00417-008-0931-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome after phototherapeutic keratectomy in patients with TGFBI-linked corneal dystrophies in relation to molecular genetic findings

Abstract: The variable genotypes in patients with TGFBI-linked corneal dystrophies lead to significantly different results after surgical treatment. The Gly623Arg mutation seems to be an optimum genotype on which to perform PTK even in older patients. It is essential to determine the genotype in order to standardize the PTK treatment and to evaluate the success in TGFBI-linked corneal dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(73 reference statements)
0
12
1
Order By: Relevance
“…It is therefore important to conduct a thorough examination to identify signs of EBMD based on corneal morphology in the absence of RCE. 26,27 In PTK treated eyes, epithelial removal was performed with a laser in 22 cases (42%) where the epithelium was smooth, similar to the method reported by Dinh et al 8 While there are a few reports of laser epithelial removal prior to PTK for EBMD, 5,6,8,24,28 the number of patients in these studies was small and the effect of epithelial removal method on outcome could not be examined. In this study, we found a borderline-significant trend towards a greater chance of recurrence with laser epithelial removal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is therefore important to conduct a thorough examination to identify signs of EBMD based on corneal morphology in the absence of RCE. 26,27 In PTK treated eyes, epithelial removal was performed with a laser in 22 cases (42%) where the epithelium was smooth, similar to the method reported by Dinh et al 8 While there are a few reports of laser epithelial removal prior to PTK for EBMD, 5,6,8,24,28 the number of patients in these studies was small and the effect of epithelial removal method on outcome could not be examined. In this study, we found a borderline-significant trend towards a greater chance of recurrence with laser epithelial removal.…”
Section: Discussionmentioning
confidence: 96%
“…The improvement in BSCVA after PTK noted in this study has also been reported by others treating EBMD patients. [5][6][7]9,13,14,16,24 No patient required a second treatment during the entire follow-up period (the single eye excluded from this study While maintenance or improvement of BSCVA is one clinical goal of PTK treatment in EBMD, prevention of recurrent erosive episodes is in many cases equally important. In 5 of 52 (9.6%) of PTK treated eyes, at least one erosive event was noted postoperatively, but erosions were mild or infrequent and did not warrant re-operation.…”
Section: Discussionmentioning
confidence: 99%
“…98, 100 The recurrence rate and the clinical features following PTK differ depending on the mutation and genotype, e.g., homozygous or heterozygous status of the patient. 101,102 The recurrent corneal deposits are denser, start at the ablation margins, and are usually observed after 7 months post-treatment. 98 Ellies et al examined the efficacy of PTK after PK in patients with various types of TGFBI-associated corneal dystrophies.…”
Section: Corneal Surface Ablationmentioning
confidence: 99%
“…Recent literature that confirms its successful use even in cases with active acanthamoeba infection [14] or in postherpetic corneal scars [3] may encourage a most liberal use of PTK in these cases. The finding that different genotypes of corneal dystrophies affect the result of PTK [11 ] can inspire further studies that may identify certain genotypes that predict better response to PTK. PTK may also be an underutilized alternative to penetrating keratoplasty in children with anterior corneal opacities that can allow for fast visual rehabilitation [13].…”
Section: Resultsmentioning
confidence: 96%
“…The surgical outcome of 12 patients with autosomal dominant transforming growth factor, beta-induced (TGFBI)-linked corneal dystrophies after PTK was correlated with the specific genotype [11 ]. It was found that the variable genotypes led to significantly different results after PTK.…”
Section: Anterior Corneal Stromal Dystrophiesmentioning
confidence: 98%